Online information for relatives of critically ill patients : Pilot test of the usability of an ICU families website - Hoffmann, M; Taibinger, M; Holl, A K; Burgsteiner, H; Pieber, T R; Eller, P; Sendlhofer, G; Amrein, K (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2019)
Relatives of intensive care patients have a very high need for information. This is due to the acute and serious, often life-threatening illness of the patients and the very complex and technical environment of an intensive care unit (ICU). Unmet needs for information can increase anxiety, sleep disorders, stress, and depressive symptoms in the relatives. The potential of the ICU families website in terms of usability and functionality during real-time testing were evaluated. The ICU families project created a dynamic online information platform in the form of a password-protected website. It contains pictures, written explanations, 5 movies, a forum and a diary function. The usability of the website was tested among 10 lay people and 10 experts (7 nurses and 3 physicians) according to the Think Aloud Method. The outcome is qualitative feedback based on video documentation by laypeople and suggestions by experts. Criticisms mentioned by the test subjects were insufficient image material, small size of the operator contact link and lack of a home button. With a mean of 9.1 (rating scale, 0 = very poor, 10 = very good), the website was almost universally recommended by the experts. This usability test of a website for relatives of ICU patients conducted among 20 test subjects showed the biggest challenges related to solving individual test scenarios and provided valuable hints for improving website usability. Features of the website highlighted as positive were the clear layout, the symbols, the diary and the consideration of children. This information was used to improve the site for subsequent roll-out in a randomized, controlled and multicentre study.